2014
DOI: 10.1177/1524838014520725
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Frequency and Impact of Stealth (Nonviolent) Gender-Based Abuse Among College Women

Abstract: The prevalence, incidence, and impact of the gender-based abuse (GBA) of college women have been increasingly documented since the 1980s, with growing precision in the measurements and expanding identification of tactics. Although there is an obvious class bias in focusing on college women (compared to women of similar ages not attending college), it is important to address GBA among this population as they are at serious risk of sexual abuse (particularly incapacitated rape), intimate partner abuse (IPA), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Therefore, both studies suggest that violence-related risk factors are particularly influential in police interpretations of risk, providing an insight into the police mind-set or schema when dealing with domestic abuse. The research reflects long-standing community, cultural and criminal justice conceptualisations of domestic abuse which have been criticized for predominantly focussing on physical violence when a broad range of harmful behaviours, both violent and non-violent, are often involved and which require identification and intervention by practitioners (Dutton and Goodman 2005, Stark 2007, Belknap and Sharma 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both studies suggest that violence-related risk factors are particularly influential in police interpretations of risk, providing an insight into the police mind-set or schema when dealing with domestic abuse. The research reflects long-standing community, cultural and criminal justice conceptualisations of domestic abuse which have been criticized for predominantly focussing on physical violence when a broad range of harmful behaviours, both violent and non-violent, are often involved and which require identification and intervention by practitioners (Dutton and Goodman 2005, Stark 2007, Belknap and Sharma 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to the recently published Campus Climate Survey on Sexual Assault and Sexual Misconduct administered at the University of Pennsylvania, 3.1% of undergraduates reported that they had been stalked while attending the university (Cantor et al, 2015). Numerous studies of college student populations report similarly high rates of stalking victimization (e.g., Belknap & Sharma, 2014; Buhi, Clayton, & Surrency, 2009; McNamara & Marsil, 2012).…”
Section: Stalking Victimizationmentioning
confidence: 99%
“…Of male victims, 43% were stalked by only male perpetrators and 45.7% were stalked by only female perpetrators. (Smith et al, 2017, p. 4) College students appear to be at particular risk for stalking victimization, with estimates frequently topping those of general population samples (e.g., Belknap & Sharma, 2014;Fisher, Daigle, & Cullen, 2010). For example, Fisher et al (2002) estimated that 13.1% of their national sample of college women had been stalked since the start of the academic year.…”
Section: Stalking Victimizationmentioning
confidence: 99%
“…The latter point is important to understand, considering that research has suggested that physical violence may neither be the most common nor the most significant aspect of an abusive relationship. In their recent analysis of non-violent gender-based abuse of college women, Belknap and Sharma (2014) concluded that they "can be some of the most terrifying, intrusive, confusing, and demeaning behaviors" (p. 182) for victims to experience. Furthermore, studies have shown that emotional pain has more lasting negative impacts when compared to physical pain (Chen, Williams, Fitness, & Newton, 2008;Hamby, 2004).…”
Section: Beyond Physical Abuse: Victimisation Experiencesmentioning
confidence: 99%
“…For example, in 2012, the UK revised the official definition to include coercive controlling behaviours, highlighting the importance of non-physical and chronic forms of offending. Despite these progressive changes, research reveals that non-violent abuse is often minimised by criminal justice actors (Belknap & Sharma, 2014). The concept of coercive control appears particularly important for recognition and effective action by police.…”
Section: Beyond Physical Abuse: Police and Legal Responsesmentioning
confidence: 99%